Incidence and progression of dental erosion among adolescents in Troms. Data based on Fit Futures - a health survey among adolescents - Hagerup, Tina-Anita Dahl; Gjerstad, Johanne Oxlund (UiT Norges arktiske universitet, 2015)
Caries and periodontitis has for a long time been the main concern among dental practitioners and a lot of research has been directed towards the management of these oral diseases. An improvement of oral health has been observed in most industrialized countries during the last 40 years, mostly due to a decline in caries prevalence in the western part of the world. However, during the last 15 years there has been an increased focus from clinicians and researchers on pathological tooth wear caused by acid erosion. Objective: The objective of the thesis was to record the incidence and determine whether there was any progression of dental erosion over a two-year period among adolescents in Northern Norway. Method: The study participants were school students from Tromsø and Balsfjord. A total of 1038, 15-18-years of age participated. The patients were examined clinically and clinical photos where taken. The progression of the dental erosive lesions were studied and scored using the Visual Erosion Dental Examination system (VEDE). Results: Results showed that dentine lesions were mostly found in lower first molars, whereas lesions restricted to enamel dominated in upper anterior teeth. We also registered cuppings and the majority was seen on the lower first molars. Of the participants registered with erosive lesions, were 62% registered with cuppings, out of which 85% where on the first molars. The cuppings were usually in addition to erosive lesions on other surfaces. Conclusion: In this study, dental erosion did not progress markedly over a two year period when assessed by comparing clinical photos, less than reported in other studies. However, the incidence was relatively high. Increasing prevalence of dental erosion during the last two decades require further cross-sectional and longitudinal prevalence studies.